ANALISIS PERBANDINGAN KINERJA ANTARA KARYAWAN OUTSOURCING DAN KARYAWAN TETAP PADA BANK BRI RANGKASBITUNG - Pipin Suryanisari; Muhamad Bustomi (The Asia Pacific Journal Of Management Studies, 2018)
Bank BRI Rangkasbitung is a work unit within the Lebak Regency Government with its reputation as a microbanking that has been rooted in the Indonesian community, BRI is constantly developing its services in accordance with the needs of the Indonesian people. This can be seen from BRI's efforts in aligning its business with the demographic development of the community that spreads to the urban area, which is marked by the emergence of new economic centers throughout Indonesia.This research has problem formulation : 1) What is the level of performance of outsourcing employees at BRI Bank Rangkasbitung Branch? (2) How does the performance level of permanent employees at BRI Bank Rangkasbitung Branch? (3) Is there a difference in performance between outsourcing employees and permanent employees at BRI Bank Rangkasbitung Branch?This study has the objectives: (1) To determine the performance of outsourcing employees at BRI Bank Rangkasbitung branch (2) To find out how the performance of permanent employees at BRI Bank Rangkas Branch count (3) To find out whether there are differences in performance between outsourcing employees and permanent employees at BRI Bank Rangkasbitung Branch.Based on the results of data processing on the reliability validity test, and normality, a significant test using Homogeneity test and independent t-test, all by using spss version 20 calculations. It is known that all outsourcing employee performance statements, and permanent employee performance produce t- test of 0, 594 which means greater than 0.05. So, it can be stated that Ha is rejected or not proven true. As seen from the section t-test for equality of means, the numbers in the column Difference mean 1.121 derived from the average method X test minus the average value of the method Y test (36,35-37,47) obtained said " There is no significant difference in the performance of Outsourcing employees towards the performance of permanent employees at Bank Rakyat Indonesia Branch Rangkasbitung